Get it right : a pocket guide to written English - Temple, Michael (John Murray LondonGB, 1987)
Aims to help reader identify and correct faults in written English. Provides notes and hints on spelling, punctuation, summarising, essay and formal letter writing, notetaking and notemaking. Defines parts of speech, phrases, clauses, sentences, paragraphs and figures of speech, giving examples.